Optical properties of erbium zinc tellurite glass system - Ab. Aziz, Sidek; El-Mallawany, Raouf A. H.; Badaron, Siti Shawaliza; Mohamed Kamari, Halimah; Matori, Khamirul Amin (Hindawi Publishing Corporation, 2015)
Er3+-doped tellurite glasses with molar compositions of xEr2O3-20ZnO-(80 - x)TeO2 (x = 0, 1, 2, 3, and 4 mole%) (EZT) have been successfully synthesized by the melt-quenching method. Density and molar volume have been measured. UV-VIS absorption spectra in the wavelength range of 400-800 nm at room temperature has been measured. The band gap for every composition has been calculated. Photoluminescence spectroscopy in the wavelength range of 400-650 nm and at room temperature has been evaluated.